Electron paramagnetic resonance (EPR) spectroscopy - Khulbe, K. C. (Elsevier Inc., 2017)
This chapter consists of the following three parts.1.The principle of electroparamagnetic resonance (EPR)2.Review on the application of EPR for membrane characterization3.Future potential of EPR application for membrane characterizationIn part 1, the fundamentals of the EPR spectroscopy is briefly outlined. Part 2 summarizes the EPR characterization work that has been already done. Interestingly, the presence of free radicals was detected in synthetic polymeric membranes, which may affect the material transport through the membrane. The incorporation of spin probe in the membrane allows the investigation of morphology as well as material transport of the reverse osmosis and ultrafiltration membrane. The electron spin resonance technique also allows the study of the membrane fouling. In part 3, the potential of EPR technique for other studies such as membrane aging and state of interfacial water in the membrane is shown. As well, EPR technique will enable the investigation of novel membrane materials such as carbon nanotubes and metal organic frameworks.